2016
DOI: 10.1099/mgen.0.000064
|View full text |Cite|
|
Sign up to set email alerts
|

In silico serotyping of E. coli from short read data identifies limited novel O-loci but extensive diversity of O:H serotype combinations within and between pathogenic lineages

Abstract: The lipopolysaccharide (O) and flagellar (H) surface antigens of Escherichia coli are targets for serotyping that have traditionally been used to identify pathogenic lineages. These surface antigens are important for the survival of E. coli within mammalian hosts. However, traditional serotyping has several limitations, and public health reference laboratories are increasingly moving towards whole genome sequencing (WGS) to characterize bacterial isolates. Here we present a method to rapidly and accurately ser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
146
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 57 publications
0
146
0
2
Order By: Relevance
“…The superiority of sequence typing over serotyping is illustrated by the ST131 UPEC pandemic strain, in which most isolates are serotype O25b:H4, but some are serotype O16:H5 (Nicolas-Chanoine et al, 2014). Importantly, E. coli serotypes can be reliably predicted from whole genome sequences (Ingle et al, 2016b). Indeed, in-silico serotyping offers a number of advantages over traditional serotyping, including the non-reliance on typing sera that may vary in quality, and the ability to type strains that do not express the O- or H-antigens in vitro or that autoagglutinate (Ingle et al, 2016b).…”
Section: E Coli Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…The superiority of sequence typing over serotyping is illustrated by the ST131 UPEC pandemic strain, in which most isolates are serotype O25b:H4, but some are serotype O16:H5 (Nicolas-Chanoine et al, 2014). Importantly, E. coli serotypes can be reliably predicted from whole genome sequences (Ingle et al, 2016b). Indeed, in-silico serotyping offers a number of advantages over traditional serotyping, including the non-reliance on typing sera that may vary in quality, and the ability to type strains that do not express the O- or H-antigens in vitro or that autoagglutinate (Ingle et al, 2016b).…”
Section: E Coli Subtypesmentioning
confidence: 99%
“…Importantly, E. coli serotypes can be reliably predicted from whole genome sequences (Ingle et al, 2016b). Indeed, in-silico serotyping offers a number of advantages over traditional serotyping, including the non-reliance on typing sera that may vary in quality, and the ability to type strains that do not express the O- or H-antigens in vitro or that autoagglutinate (Ingle et al, 2016b). For these reasons, in-silico serotyping is likely to replace traditional serotyping in future.…”
Section: E Coli Subtypesmentioning
confidence: 99%
“…It has also recently been shown that antimicrobial resistance (Tyson et al, 2015; McDermott et al, 2016; Zhao et al, 2016), serovar (Levine et al, 2016; Yoshida et al, 2016b), and the results of other traditional sub-typing schemes such as multi-locus sequence typing (Sheppard et al, 2012) can be accurately predicted in silico through the analysis of bacterial genome sequences. However, identifying bacterial isolates that are most likely to cause disease in humans, based on the genome sequence alone, is a more complex task.…”
Section: Introductionmentioning
confidence: 99%
“…Both use antisera in simple agglutination assays. To date, over 180 E. coli O‐serogroups and over 50 H‐serotypes have been identified (Ingle et al., ) and there are more than 100 serotypes of STEC associated with human disease (Ferdous et al., ). Surveillance of STEC infections is often undertaken using serotyping (full or partial) only or using methods which only recover and identify O157:H7 strains.…”
Section: Epidemiology Source Attribution and Risk Assessmentmentioning
confidence: 99%